Fundamentos de la educación ambiental - Montaña, Vilma Hernández (Tecnogestión: Una mirada al ambiente, 2006)
Always the human species has interactive with the means and it has modified it, the environmental problems are not new. However, that makes preocupate especially the current situation it is the acceleration of those modifications, their massive character and the universality of their consequences. The environmental problems no longer appear as independent some of other but rather they constitute elements that are related configuring a reality different to the simple accumulation of all to each other them. For it, today in day we can speak of something more than of simple environmental problems, we face an authentic environmental crisis and the graveness of the crisis is manifested in its global character. However, we cannot limit ourselves to perceive this crisis like conflict in the one that certain positions on the world and envelope the life is inadequate. If we are aware that only in a crisis atmosphere they are considered and innovative solutions are developed, it seems clear that have before us the challenge of finding in the crisis an occasion for to reinvent in a creative way our way to understand and to be related with the world. But these solutions cannot be solely technological, the environmental challenge supposes a challenge since to the values of the contemporary society those values that sustain the human decisions, they are in the root of the environmental crisis. In this context, the environmental education has an important paper that to play when confronting this challenge, promoting a innovative learning characterized by the anticipation and the participation that he/she only allows not to understand, but also to be implied in that that we want to understand found of the environmental education